Filogenia e evolução dos misticetos (Mammallia : cetartiodactyla) com uma abordagem genômica - Trujillo, Olga Lucia Herrera (2021)
The evolutionary history of the baleen whales (Mysticeti) has been difficult to establish based on morphological and molecular data. The main inconsistencies refer to the relationship between the gray whale and the main Balaenopteridae clades, with the morphological characters supporting monophyletic Balaenopteridae. At the same time, the molecular data favored the paraphyly of Balaenopteridae with the inclusion of Eschrichtiidae, symbolizing a long history of conflict between the two hypotheses. Additionally, despite having a wide distribution, many baleen whales have structured populations between different ocean basins. No comparative analysis of this population structure among baleen whales with the same type of molecular data was done so far and among their demographic history. Here we analyzed 28 genomes from 12 of 15 whale species to resolve these long-standing questions about Mysticeti evolution and evaluate patterns on their demographic history and divergence times between populations. We found that the gray whale is the remnant of an archaic lineage sister to rorquals whose genome has been largely (~87%) substituted by two massive introgressions from rorqual´s lineages. This result shows that the gray whale's benthic suction feeding mechanism did not revert from the specialized rorqual engulfment mode but likely retained an ancient morphology despite keeping only 13% of its original genome. We propose considering the complex evolutionary history depicted by past introgressions as the basis for the biological classification of the Mysticeti. We also found a general demographic pattern for all species, with a significant decline in effective population sizes (Ne) from the Plio-Pleistocene Transition to approximately the Middle Pleistocene Transition and the MIS 11 (400 ka) associated with the final establishment of gigantism and a decrease in the carrying capacity of the oceans at high latitudes due to the drop in primary productivity. We also found that current populations began to diverge around MIS 11 and that gene flow was maintained for a long time after the initial population divergences. After MIS 11 we identified a pattern of expansion in populations in the Southern Hemisphere, while those in the North Pacific maintained a reduced Ne. Our results suggest an association in factors that promote diversification and changes in the population size of the baleen whales, although we cannot explain the demographic expansion found in the populations of the Southern Hemisphere.